Exploring the Effect of Music in Promoting the Health and Well-being of University Students in the COVID-19 Era - Fatih Şekercioğlu; Noori Kım (Journal of Economy Culture and Society)
The therapeutic effect of music on mental and physical health is a well-known fact. However, there is a knowledge gap in understanding music’s effect on university students coping with the mental health effects of the COVID-19 pandemic. The qualitative analysis method has been used in the research. In this context, an online survey has prepared and presented to the participants. NVIVO 12™, a qualitative data analysis method, has been used to evaluate the survey results. Our study demonstrates that physical distancing measures negatively impact university students’ mental health (e.g., stress, depression, anxiety) due to a lack of social interaction, support and the distinction between study and rest areas during the COVID-19 pandemic. Our study also reports diverging opinions regarding the virtual learning system. Some students expressed positivity towards the virtual learning system due to the absence of commuting stress and flexibility. However, many students still answered negatively due to perceived lowered lecture quality and the challenge of adjusting to the new educational environment. Musical experiences were found to be effective coping strategies that help maintain well-being and health among students due to their effectiveness in immediate mood change and distraction from reality.